Money, Gender, and Self-Efficacy: Ethical Perceptions of Accounting Students: Uang, Gender, dan Diri Sendiri: Persepsi Etika Mahasiswa Akuntansi - Jihan Fadhila; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to investigate the impact of love of money, gender, and socio-economic status on the ethical perceptions of accounting students, while considering self-efficacy as an intervening variable. A quantitative approach was adopted, and a total of 134 respondents from Muhammadiyah University of Sidoarjo were selected using a stratified random sampling method. Structural Equation Modeling (SEM) based on Variance - PLS was utilized for hypothesis analysis. The findings revealed that love of money did not significantly affect ethical perceptions, whereas gender and socio-economic status exhibited significant effects. Furthermore, self-efficacy was found to significantly influence ethical perceptions, acting as a mediator between love of money and ethical perceptions, as well as socio-economic status and ethical perceptions. However, gender did not have a direct or significant effect on self-efficacy. These results contribute to the understanding of factors influencing ethical perceptions among accounting students and highlight the importance of considering self-efficacy as a mechanism through which love of money and socio-economic status affect ethical decision-making. Highlights: The role of self-efficacy: Self-efficacy plays a significant mediating role in the relationship between love of money, socio-economic status, and ethical perceptions of accounting students. Gender differences in ethical perceptions: Gender was found to have a notable impact on the ethical perceptions of accounting students, indicating the need for further exploration of gender-related factors influencing ethical decision-making. Socio-economic status and ethical perceptions: The study highlights the influence of socio-economic status on the ethical perceptions of accounting students, emphasizing the importance of considering socio-economic factors in ethical education and training for future accountants. Keywords: Love of Money, Gender, Socio-Economic Status, Ethical Perceptions, Self-Efficacy